Long Non-Coding RNA PNKY Modulates the Development of Choroidal Neovascularization - Shi, Lianjun; Han, Xue; Liu, Chang; Li, Xiumiao; Lu, Shuting; Jiang, Qin; Yao, Jin (Frontiers in Cell and Developmental Biology, 2022)
Long non-coding RNAs (lncRNAs) have been widely implicated in human diseases. Our aim was to explore the regulatory role of changes in the expression levels of PNKY and its linked signaling networks in mediating stress induced choroidal neovascularization. PNKY expression levels were reduced in mice by laser and exposure of endothelial cell to a hypoxic stress. PNKY silencing led to formation of CNV in laser-induced CNV model and in the ex-vivo model, while overexpression inhibited CNV development. Silencing or overexpression of PNKY altered the viability, proliferation, migration and tube-forming capacity of endothelial cells in vitro. Mechanistically, through lncRNA - RNA binding protein - miRNA interaction analysis involving loss of function and gain-of-function experiments, we found that lncRNA PNKY inhibited the binding of miR124 to PTBP1 and maintained the homeostasis of choroidal vascular function by promoting Bcl-2 like protein 11 (BIM), and its dysfunction led to exacerbation of CNV lesion. Therefore, this study suggests that the lnc PNKY/PTBP1-miR-124 axis is involved in regulating the development of CNV, providing a potential therapeutic target for the treatment of CNV.